Enhancing Data Security and Integrity with Post-Quantum and AES Digital Signatures - Rayasa Puringgar Prasadha Putra; H. A. Danang Rimbawa; Bisyron Wahyudi (Jurnal Komputer, Informasi dan Teknologi, 2024)
Data security and integrity are crucial issues in contemporary information systems, since the emergence of quantum computing presents substantial risks to traditional cryptographic techniques such as RSA and ECC. This work suggests a hybrid technique that combines the Advanced Encryption Standard (AES) for symmetric encryption with Post-Quantum Cryptography (PQC) digital signatures to mitigate these issues. The framework seeks to safeguard sensitive documents, including PDFs, against unauthorized alterations and Man-in-the-Middle (MiTM) attacks. A simulation is executed to illustrate the threats associated with Man-in-the-Middle (MiTM) attacks, whereby the encrypted document and digital signatures are intercepted, altered, and re-encrypted. The technology guarantees data integrity by signature verification and hash comparisons, efficiently identifying and preventing tampering. The findings indicate that the suggested PQC-AES hybrid system not only fortifies defenses against conventional threats but also improves resistance to quantum-based assaults, offering a scalable and safe approach for contemporary data security. The research emphasizes the need of implementing quantum-resistant algorithms to safeguard digital security systems for the future, while preserving the efficacy of existing encryption techniques. The progression of quantum computing presents substantial threats to traditional cryptography methods, including RSA and ECC. These cryptosystems depend on mathematical issues that can be effectively resolved using quantum algorithms, especially Shor's algorithm. Post-Quantum Cryptography (PQC) has emerged as a viable way to mitigate this issue